State Intervention in Air Transport: Experience from the Republic of Indonesia - Simatupang, Andika Immanuel (UI Scholars Hub, 2019)
State intervention of the air transport industry is a widespread practice throughout the world where this kind of interference from the government to the air transport industry could be in the form of state aid or state subsidies. This paper attempts to explain the impact of state aid in the competition of air transport in The Republic of Indonesia resulting distortion in the competition of the aviation industry. This paper examines the state aid practice in The Republic of Indonesia and attempts to answer the debate whether this practice resulting in an unfair competition and violating level playing field in air transport in Indonesia or such method then creates an efficiency in air transport in Indonesia which makes it a good policy. However, this paper will not look into the analysis of the difference between terminologies on State aid and State subsidies.